Ecosystem Services as a Contested Concept: a Synthesis of Critique and Counter‐Arguments. Issue 6 (17th February 2014) - Schröter, Matthias; van der Zanden, Emma H.; van Oudenhoven, Alexander P.E.; Remme, Roy P.; Serna‐Chavez, Hector M.; de Groot, Rudolf S.; Opdam, Paul
Abstract We describe and reflect on seven recurring critiques of the concept of ecosystem services and respective counter‐arguments. First, the concept is criticized for being anthropocentric, whereas others argue that it goes beyond instrumental values. Second, some argue that the concept promotes an exploitative human–nature relationship, whereas others state that it reconnects society to ecosystems, emphasizing humanity's dependence on nature. Third, concerns exist that the concept may conflict with biodiversity conservation objectives, whereas others emphasize complementarity. Fourth, the concept is questioned because of its supposed focus on economic valuation, whereas others argue that ecosystem services science includes many values. Fifth, the concept is criticized for promoting commodification of nature, whereas others point out that most ecosystem services are not connected to market‐based instruments. Sixth, vagueness of definitions and classifications are stated to be a weakness, whereas others argue that vagueness enhances transdisciplinary collaboration. Seventh, some criticize the normative nature of the concept, implying that all outcomes of ecosystem processes are desirable. The normative nature is indeed typical for the concept, but should not be problematic when acknowledged. By disentangling and contrasting different arguments we hope to contribute to a more structured debate between opponents and proponents of the ecosystem services concept.